Knowledge management to boost productivity in manufacturing - Mansor, M. A.; Ismail, A. R.; Hamran, N. N. N.; Sarifudin, M. S. (University of El Qued (Algeria), 2018)
Data are the crucial element for productivity improvement and the evaluation or measurement process in the manufacturing sector because the data can tell the real situation about the production site. The dataare useful for productivity improvement by using certain lean manufacturing’s tools such as Value Stream Mapping (VSM), Single Minutes of Exchange Die (SMED), Total Productive Maintenance (TPM), and others. The data are also necessary for performance measurement. In this paper, we discuss the necessary data that should be included in a knowledge repository for manufacturing where the data then will be used by an assessment tool. The assessment tool is an important factor because knowledge management has a deep relationship with performance evaluation and measurement. Data Management to boost productivity in manufacturing can be divided into five phase and consists of in fourteen steps.